An open chat with…Takashi Gojobori. Issue 2 (17th January 2022) - Wright, Duncan; Gojobori, Takashi
Abstract : Takashi Gojobori was one of the original founding members of the Editorial Board of FEBS Open Bio and is easily one of our most hard‐working editors, having carefully evaluated hundreds of manuscripts on bioinformatics for us over the last decade. Takashi Gojobori received his doctorate at Kyushu University, Japan, before joining the University of Texas Health Science Center as a Research Associate and then Research Assistant Professor. Takashi was formerly the Vice‐Director and Professor of National Institute of Genetics (NIG), Mishima, Japan, and at present, he is Distinguished Professor of Bioscience and Bioscience Acting Director of the Computational Bioscience Research Center at King Abdullah University of Science and Technology (KAUST), Saudi Arabia. Takashi was formerly the Editor‐in‐Chief of the journal Gene and is also a long‐term member of the Editorial Board of FEBS Letters, among other editorial appointments. In honour of his 10 years (and counting!) of service to the journal, we present here this interview with him on his research and experiences. Abstract : Takashi Gojobori was one of the original founding members of the Editorial Board of FEBS Open Bio and is easily one of our most hard‐working editors, having carefully evaluated hundreds of manuscripts on bioinformatics for us over the last decade. In honour of his 10 years (and counting!) of service to the journal, we present here this interview with him on his research and experiences.